Portfolio of prospective clinical trials including brachytherapy: an analysis of the ClinicalTrials.gov database. Issue 1 (December 2016) - Cihoric, Nikola; Tsikkinis, Alexandros; Miguelez, Cristina; Strnad, Vratislav; Soldatovic, Ivan; Ghadjar, Pirus; Jeremic, Branislav; Dal Pra, Alan; Aebersold, Daniel; Lössl, Kristina
Abstract Background To evaluate the current status of prospective interventional clinical trials that includes brachytherapy (BT) procedures. Methods The records of 175, 538 (100 %) clinical trials registered at ClinicalTrials.gov were downloaded on September 2014 and a database was established. Trials using BT as an intervention were identified for further analyses. The selected trials were manually categorized according to indication(s), BT source, applied dose rate, primary sponsor type, location, protocol initiator and funding source. We analyzed trials across 8 available trial protocol elements registered within the database. Results In total 245 clinical trials were identified, 147 with BT as primary investigated treatment modality and 98 that included BT as an optional treatment component or as part of the standard treatment. Academic centers were the most frequent protocol initiators in trials where BT was the primary investigational treatment modality (p < 0.01). High dose rate (HDR) BT was the most frequently investigated type of BT dose rate (46.3 %) followed by low dose rate (LDR) (42.0 %). Prostate was the most frequently investigated tumor entity in trials with BT as the primary treatment modality (40.1 %) followed by breast cancer (17.0 %). BT was rarely the primary investigated treatment modality for cervical cancer (6.8 %). Conclusion Most clinical trials using BT are predominantly in early phases, investigator-initiated and with low accrual numbers. Current investigational activities that include BT mainly focus on prostate and breast cancers. Important questions concerning the optimal usage of BT will not be answered in the near future.